Should we let employees contract away their rights against arbitrary discharge? - Phillips, Michael J. (Journal of business ethics, 1994)
This article argues that the moral right to be discharged only for good cause and like rights can be contracted away by employees in appropriate circumstances. It maintains that the rights in question are not inalienable, and that there is nothing irrational about an employee's wishing to deal them away. It also maintains that inequalities in bargaining power between employers and employees are insufficiently pervasive to justify a flat ban on the alienation of these rights. For a waiver of such rights to be valid, however, employees must have full knowledge of its terms., The question addressed here bears on several legal and policy issues affecting termination of the employment relation. If employees can contract away their right to a goodcause discharge, the American doctrine of employment at willmight find justification in the face of that right. In addition, the alienability of such discharge rights may be necessary to justify express disclaimers of wrongful discharge liability and the waiver provision of the new U.S. Draft Uniform Employment-Termination Act.